Smart Cap - Larry S. Karp; Christian Träger (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We introduce a “smart” cap and trade system that eliminates the welfare costs of asymmetric information (“uncertainty”). This cap responds endogenously to technology or macroeconomic shocks, relying on the market price of certificates to aggregate information. It allows policy makers to modify existing institutions to achieve more efficient emission reductions. The paper also shows that the efficient carbon price is more sensitive to technological innovations than usually assumed. The lasting impact and slow diffusion of these innovations typically make the optimal carbon price a much steeper function of emissions than suggested by the social cost of carbon.
Keywords: Q00; Q50; H20; D80; 330; pollution; climate change; taxes; quantities; regulation; smart cap; uncertainty; technology diffusion; dynamic programming; integrated assessment; DICE